Know Your Place - Ellis, Shelly (New York, NY Dafina Books/Kensington Publishing Corp., 2019)
"Success didn't come easy for three best friends from the streets. And now dangerous choices and reckless desire will push their bond to lethal limits."--Publisher's description.
Their stint at the Branch Avenue Boys' Youth Institute taught Ricky, Derrick, and Jamal to unite when the going got tough... and things are really tough right now. Arrested during a raid, Ricky must inform on D.C's drug king pin, Dolla Dolla-- and find the woman who loved and betrayed him. One of Institute head Derrick's students is hiding Dolla Dolla's major stash, and attempt to do the right thing will have shattering consequences. Jamal's backroom deal with D.C.'s corrupt mayor is giving him everything he thought he wanted, but the return of the woman he's always loved is getting him in way over his head. -- adapted from back cover
Keywords: African American men -- Fiction; Best friends -- Fiction; Street life -- Fiction; Male friendship -- Fiction; Drug dealers -- Fiction; Politicians -- Fiction; African American men; Best friends; Street life; Fiction; Romance fiction; Urban fiction; Urban fiction